Soybean (Glycine max L. Merrill) responds to phosphorus application and rhizobium inoculation on Acrisols of the semi-deciduous forest agro-ecological zone of Ghana - Adjei-Nsiah, S.; Martei, D.; Yakubu, S.A.; Ulzen, J. (PeerJ, 2022)
Soybean cultivation in Ghana is limited mainly to the Guinea savanna and the forest/savanna transitional agro-ecological zones. Although soybean can be cultivated in the semi-deciduous forest zone, low soil pH and limited nodulation limit its productivity in this zone. In this study, a randomized complete block design, with four replications, was used to test if rhizobia inoculation and/or p-fertilizer could improve yield of soybean in the semi-deciduous forest zone. The residual effects of the treatments were tested on maize and soybean sequentially during the 2018 and 2019 cropping seasons. The inoculation study was repeated in 2020. Phosphorus and inoculation significantly (p = 0.0009) increased soybean grain yield in the 2018 cropping season by 88% and 108%, respectively over the control. Co-application of P and inoculant increased grain yield 3-fold over the control. Maize grain yield ranged from 4.3 t ha−1 in the control plots to 5.2 t ha−1 in treated plots but did not differ significantly among treatments. In 2020, the combined application of P and inoculant produced a significantly (0.002) higher yield than any of the other treatments. This demonstrates that soybean can be grown economically in the semi-deciduous forest agro-ecological zone of Ghana. Co-application of P and inoculant appeared cost-effective, in terms of return on investment.